Sobre a analgesia pós-operatória da morfina, cetamina ou da associação em cadelas submetidas à ovariossalpingohisterectomia eletiva - de Almeida, Maria Raquel [UNESP]; Luna, Stélio Pacca Loureiro [UNESP]; Alves, Robson Moreira; Hashimoto, Hetielle Harumi; de Almeida, Ricardo Miyasaka (FapUNIFESP (SciELO), 2013)
This study aimed to evaluate the post operative analgesic effects of morphine or ketamine alone or their combination in 24 healthy bitches, weighing 11.01±8.69kg and aging 27±17 months, submitted to elective ovariohysterectomy. The animals were distributed to one of the three treatments after the anaesthetic induction: morphine (GM, n=8, 0.5mg kg-1 IM), ketamine (GK, n=8, 2.5mg kg-1 IM) or ketamine combined to morphine (GKM) using the same doses previously described. Sedation score and pain assessment were performed blindly two hours before surgery and at 1, 2, 4, 8, 12, and 24 hours after extubation, using the Dobbins scale (sedation) and visual analogue scale (pain) and Glasgow modified pain scale (GMPS). Rescue analgesia was performed with 1.0mg kg-1 of morphine and if not sufficient, followed by 0.2mg kg-1 of meloxicam, both IM, when the GMPS reached above 33% of the total score. Non parametric data were analyzed using Friedmańs test followed by Dunńs test for differences in time. Kruskal-Walliś test followed by Dunńs test were used to investigate differences in the number of analgesic rescues and among groups at each time. Parametric data were evaluated by ANOVA followed by Tukey's test (P<0.05). Except for GMPS, where the values of GM were greater than for GKM at 1h post-extubation, there were no other differences among groups. The number of rescue analgesia was greater in GM (11 in total; twice in 3 animals,) when compared to GKM (3; twice in 1 animal) and GK (2; twice in 1 animal). Analgesia provided by pre-incisional ketamine was more effective when compared to morphine. According to that, ketamine alone may be used as a preemptive analgesic in bitches undergoing ovariohysterectomy; however, rescue analgesia may be necessary.
About post operatory analgesia of morphine, ketamine or their combination in bitches undergoing elective ovariohysterectomy
Keywords: Analgesia; Dogs; Opioid; Phencyclidine